2010
DOI: 10.1007/s00247-009-1497-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal gastrointestinal MRI: all that glitters in T1 is not necessarily colon

Abstract: In cases of fetal occlusion, T1 hypersignal should not be considered as a sign of distal ileal or colonic occlusion. The obstruction may be proximal, implying a risk of small bowel syndrome, which requires adequate parental counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Our data support previously reported studies that the MRI signal of dilated loops is helpful in better localizing the level of obstruction. Regarding the dilated bowel proximal to the obstruction, high T2 signal in the dilated bowel was mainly observed in cases of proximal obstruction, as previously suggested by the Colombani et al [17] and Furey et al [18] series. Rubio et al's [2] series described low T1 signal to describe proximal jejunal atresia, and the studies by Saguintaah et al [19] and Shinmoto et al [20] have suggested that the higher the signal on T1-weighted images, the more distal the atresia.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our data support previously reported studies that the MRI signal of dilated loops is helpful in better localizing the level of obstruction. Regarding the dilated bowel proximal to the obstruction, high T2 signal in the dilated bowel was mainly observed in cases of proximal obstruction, as previously suggested by the Colombani et al [17] and Furey et al [18] series. Rubio et al's [2] series described low T1 signal to describe proximal jejunal atresia, and the studies by Saguintaah et al [19] and Shinmoto et al [20] have suggested that the higher the signal on T1-weighted images, the more distal the atresia.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, despite the long study period, the size of our study population remains small, and the exact impact of preterm delivery could not be appropriately taken into account. The absence of any diagnosis of cystic fibrosis in our se-ries might be surprising to some readers, given that it is a relatively frequent and well-known cause of prenatal bowel obstruction [2,17]. However, in our center, most cases were diagnosed by early genetic testing prior to MRI examinations, and many parents subsequently chose to terminate the pregnancy, in accordance with French law.…”
Section: Discussionmentioning
confidence: 82%
“…The false‐positive rate of detecting ND‐SBA by ultrasound is another relevant issue. The positive predictive value of prenatal ultrasound has been reported to be variable, ranging between 3% and 90%. Although the current systematic review was not designed specifically to investigate false‐positive rate, two studies reported the false‐positive rate of detecting ND‐SBA by ultrasound and provided an overall positive predictive value of 47.1% (95% CI, 23.0–72.2%).…”
Section: Discussionmentioning
confidence: 90%
“…2 In recent years, there is increasing evidence on the diagnostic potential of fetal magnetic resonance imaging (MRI) for fetal intestinal abnormalities. [1][2][3][4][5][6][7][8] The use of single-short fast spin-echo T2-weighted sequences for the evaluation of the expected location and morphology of fluid-containing structures, including the stomach and small bowel, and T1-weighted imaging for signal intensity characteristics of the fetal meconium, the normal pattern of the meconium with advancing gestation age, and the expected caliber of the small and large bowel in the fetus are key to the diagnoses of abnormalities of the gastrointestinal tract. 3 However, there are few large series on prenatally diagnosed fetal intestinal obstruction by MRI, especially combined with the operation results.…”
Section: Introductionmentioning
confidence: 99%